Optimization of high-solid enzymatic hydrolysis of two-step alkaline and dilute acid-pretreated sugarcane bagasse at low enzyme loadings by response surface methodology - Igbojionu, Longinus Ifeanyi [UNESP]; Laluce, Cecilia [UNESP] (Springer Nature, 2021)
Sugarcane bagasse—a lignocellulosic material derived from sugarcane after crushing and extracting of its juice—is a promising feedstock for bioethanol production. The current study presented a two-step alkaline and acid pretreatment of sugarcane bagasse using sodium hydroxide and maleic acid as a strategy to enhance enzymatic digestibility of sugarcane bagasse. The two-step alkaline and acid pretreatment resulted to a significant increase in glucan content (69.72%) with accompanying decreases in xylan (12.99%) and lignin (4.89%) contents. Preliminary study on enzymatic hydrolysis of the two-step alkaline and acid-pretreated sugarcane bagasse with low solid loading and low cellulase concentrations resulted to high glucose yields. Optimization of high-solid enzymatic hydrolysis of two-step alkaline and acid-pretreated sugarcane bagasse was executed based on Box-Behnken design (BBD). BBD—a response surface methodology—is a powerful method that can be used to test several parameters by applying a minimum number of experimental trials. The optimal level of process variables as indicated by the statistical model namely solid loading (20%, w/w), incubation time (72 h), enzyme loading (2 FPU/g glucan), and substrate feeding (mode 2) were validated. Optimization of the process parameters resulted to 61.85% of glucose yield which was close to its predicted value (65.71%). The current study highlights the potential of high-solid enzymatic hydrolysis using two-step alkaline and acid-pretreated sugarcane bagasse for efficient fermentable sugar production.
Keywords: Bioethanol; Box-Behnken design; High-solid enzymatic hydrolysis; Optimization; Sugarcane bagasse; Two-step pretreatment